Bromocriptine: could it be the cure for post-surgical akinetic mutism? - Arevalo-Saenz, A; Pedrosa-Sanchez, M; Sola, R G (Revista de neurologiá, 2017)
Akinetic mutism is considered as an alteration of the motivational state of the person, which the patient is unable to initiate verbal or motor responses voluntary, even with preserved sensorimotor and surveillance functions. A 43 year-old male involved in a cerebellum arteriovenous fistula complicated with hydrocephalus, who responded dramatically to treatment with bromocriptine. Typically, akinetic mutism is described as a transient surgeries posterior fossa. However, it can also occur after multiple valvular failure in patients with hydrocephalus.